A Novel Role for the Regulatory Nod-Like Receptor NLRP12 in Anti-Dengue Virus Response - Li, Xingyu; Dong, Zhuo; Liu, Yan; Song, Weifeng; Pu, Jieying; Jiang, Guanmin; Wu, Yongjian; Liu, Lei; Huang, Xi (Frontiers in Immunology, 2021)
Dengue Virus (DENV) infection can cause severe illness such as highly fatality dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Innate immune activation by Nod-like receptors (NLRs) is a critical part of host defense against viral infection. Here, we revealed a key mechanism of NLRP12-mediated regulation in DENV infection. Firstly, NLRP12 expression was inhibited in human macrophage following DENV or other flaviviruses (JEV, YFV, ZIKA) infection. Positive regulatory domain 1 (PRDM1) was induced by DENV or poly(I:C), and suppressed NLRP12 expression, which was dependent on TBK-1/IRF3 and NF-κB signaling pathways. Moreover, NLRP12 inhibited DENV and other flaviviruses (JEV, YFV, ZIKA) replication, which relied on the well-conserved nucleotide binding structures of its NACHT domain. Furthermore, NLRP12 could interact with Heat shock protein 70 (HSP70) and HSP90 dependent on its Walker A and Walker B sites. Inhibition of HSP90 restored DENV replication suppressed by NLRP12. In addition, NLRP12 inhibited the pro-inflammatory cytokines in macrophage after DENV infection through p38/JNK MAPKs and NF-kB signaling pathways. Taken together, we demonstrated a novel mechanism that NLRP12 exerted anti-viral and anti-inflammatory properties in DENV and other flaviviruses (JEV, YFV, ZIKA) infection, which brings up a potential target for the treatment of DENV infection.